Analysis of User Behavior in Face Recognition Boarding Gate Services Towards the Satisfaction of Long-Distance Train Passengers Using the UTAUT2 Model - Amaliyah, Tazkiyatun Aeni; Putra, Anggyi Trisnawan (Journal of Advances in Information Systems and Technology, 2025)
In the era of Industry 4.0, the adoption of technology has become crucial for enhancing performance, efficiency, usability, and sustainability in various sectors, including transportation. PT Kereta Api Indonesia (Persero), the largest railway company in Indonesia, has implemented Face Recognition Boarding Gate technology to improve the passenger experience by simplifying the train departure process. However, the deployment of facial recognition technology in the transportation sector also raises significant concerns regarding data security and privacy. This study aims to analyze the impact of using Face Recognition Boarding Gate technology on the satisfaction of long-distance train passengers, employing the UTAUT2 model as a theoretical framework. The research utilizes a quantitative method with purposive sampling to select respondents, focusing on users aged 17 and above who have used the service at least once. A total of 166 valid responses were collected through online questionnaires. The collected data was processed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the aid of Google Colab. The analysis results stated that 7 out of 9 proposed hypotheses were accepted, corresponding to an acceptance rate of 77%. Specifically, performance expectancy, effort expectancy, and perceived security were found to have a direct positive impact on passenger satisfaction. Additionally, hedonic motivation and habit significantly influenced behavioral intention, which in turn had a positive effect on satisfaction and use behavior. The findings of this research provide valuable insights for service providers, highlighting the importance of addressing security and privacy concerns while enhancing the overall user experience. Furthermore, the study offers a useful reference for future researchers interested in exploring the adoption and impact of advanced technologies in the transportation sector.